Demonstration of safety of intravenous immunoglobulin in geriatric patients in a long‐term, placebo‐controlled study of Alzheimer's disease. Issue 2 (21st June 2016) - Gelmont, David; Thomas, Ronald G.; Britt, Jonathan; Dyck‐Jones, Jacqueline A.; Doralt, Jennifer; Fritsch, Sandor; Brewer, James B.; Rissman, Robert A.; Aisen, Paul
Abstract: Introduction: We present safety results from a study of Gammagard Liquid intravenous immunoglobulin (IGIV) in patients with probable Alzheimer's disease. Methods: This was a placebo‐controlled double‐blind study. Subjects were randomized to 400 mg/kg (n = 127), 200 mg/kg (n = 135) IGIV, or to 0.25% human albumin (n = 121) administered every 2 weeks ± 7 days for 18 months. Results: Elevated risk ratios of IGIV versus placebo included chills (3.85) in 9.5% of IGIV‐treated subjects (all doses), compared to 2.5% of placebo‐treated subjects, and rash (3.08) in 15.3% of IGIV‐treated subjects versus 5.0% of subjects treated with placebo. Subjects in the highest IGIV dose group had the lowest proportion of SAEs considered related to product (2 of 127 [1.6%]). Subjects treated with IGIV experienced a lower rate of respiratory and all other infections compared to placebo. Discussion: IGIV‐treated subjects did not experience higher rates of renal failure, lung injury, or thrombotic events than the placebo group. There were no unexpected safety findings. IGIV was well tolerated throughout 18 months of treatment in subjects aged 50–89 years.